(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
The victim-executioner relationship in gender-based violence in ItalySociological research on gender-based violence in recent decades has developed new approaches to reading the phenomenon, on the victim and on victimization processes given the increase in cases in Italy. The transversality of the phenomenon is traceable both in the way of looking at the victim-executioner relationship and in the social changes that this conflictual relationship also produces from the socio-economic point of view. This will be covered in this work.